Measurement and analysis of critical thinking disposition towards English language learning among secondary school students (Innovaciones Educativas, 2024)
The present study analyzes the critical thinking disposition of 205 students from public high schools regarding English language learning. A 6-point-Likert scale was applied to the participants to collect data using the Critical Thinking Disposition Scale, which consisted of 26 questions; moreover, participants’ sociodemographic characteristics were gathered. The Critical Thinking Disposition Scale comprised seven dimensions: Truth-seeking, Open-mindedness, Analyticity, Systematicity, Self-confidence Critical Thinking, Inquisitiveness, and Cognitive Maturity. The first method of data analysis was descriptive statistics, this analysis addressed the data's mean score and standard deviation, followed by a Spearman correlation analysis to find relationships among the dataset, which showed correlations among the seven dimensions but not between the dimensions and the sociodemographic information. Finally, a hierarchical cluster analysis was conducted to divide the data and respondents into four similar groups, according to their answers. The findings show that high school students present neither a strong nor weak disposition to critical thinking; their disposition is rather undefined.
Keywords: Critical thinking; English; Language learning; Public high schools; Public education